Production of Lauric Acid and Pentaerythritol Based Biolubricant - Mahmud, Hamizah Ammarah; Salimon, Jumat (Journal of Science and Technology, 2014)
Production of a biolubricant based on lauric acid and pentaerythritol (PE) was carried out. The esterification reaction at 180°C-200°C for 6-7 hours in the present of sulphuric acid as catalyst. The end product (PE ester) was confirmed through the determination of Fourier Transformation Infrared spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR), GC-FID . The characterization of PE ester’s of viscosity index, pour point, flash point and oxidative stability . The PE ester showed flash point at 250°C, pour point at 25°C, viscosity index 162 and the oxidative stability at 216°C respectively.The PE ester produced is plausible to be used as potential biolubricant.